Universities and Economic Development in Africa Pact, academic core and coordination - Cloete, Nico (African Minds, 2012)
Universities and economic development in Africa: Pact, academic core and coordination draws together evidence and synthesises the findings from eight African case studies. The three key findings presented in this report are as follows: 1. There is a lack of clarity and agreement (pact) about a development model and the role of higher education in development, at both national and institutional levels. There is, however, an increasing awareness, particularly at government level, of the importance of universities in the global context of the knowledge economy. 2. Research production at the eight African universities is not strong enough to enable them to build on their traditional undergraduate teaching roles and make a sustained contribution to development via new knowledge production. A number of universities have manageable student-staff ratios and adequately qualifi ed staff, but inadequate funds for staff to engage in research. In addition, the incentive regimes do not support knowledge production. 3. In none of the countries in the sample is there a coordinated effort between government, external stakeholders and the university to systematically strengthen the contribution that the university can make to development. While at each of the universities there are exemplary development projects that connect strongly to external stakeholders and strengthen the academic core, the challenge is how to increase the number of these projects. The project on which this report is based forms part of a larger study on Higher Education and Economic Development in Africa, undertaken by the Higher Education Research and Advocacy Network in Africa (HERANA). HERANA is coordinated by the Centre for Higher Education Transformation in South Africa.